In vivo Protein Corona Formation: Characterizations, Effects on Engineered Nanoparticles’ Biobehaviors, and Applications - Bai, Xue; Wang, Jiali; Mu, Qingxin; Su, Gaoxing (Frontiers in Bioengineering and Biotechnology, 2021)
Understanding the basic interactions between engineered nanoparticles (ENPs) and biological systems is essential for evaluating ENPs’ safety and developing better nanomedicine. Profound interactions between ENPs and biomolecules such as proteins are inevitable to occur when ENPs are administered or exposed to biological systems, for example, through intravenous injection, oral, or respiration. As a key component of these interactions, protein corona (PC) is immediately formed surrounding the outlayer of ENPs. PC formation is crucial because it gives ENPs a new biological identity by altering not only the physiochemical properties, but also the biobehaviors of ENPs. In the past two decades, most investigations about PC formation were carried out with in vitro systems which could not represent the true events occurring within in vivo systems. Most recently, studies of in vivo PC formation were reported, and it was found that the protein compositions and structures were very different from those formed in vitro. Herein, we provide an in-time review of the recent investigations of this in vivo PC formation of ENPs. In this review, commonly used characterization methods and compositions of in vivo PC are summarized firstly. Next, we highlight the impacts of the in vivo PC formation on absorption, blood circulation, biodistribution, metabolism, and toxicity of administered ENPs. We also introduce the applications of modulating in vivo PC formation in nanomedicine. We further discuss the challenges and future perspectives.